Virtue and reason in Plato and Aristotle - Price, A. W. (Oxford : Oxford University Press, 2011)
Price explores the views of Plato and Aristotle on how virtue of character and practical reasoning enable agents to achieve eudaimonia - the state of living or acting well. He provides a philosophical analysis and argues that the perennial question of action within human life is central to the reflections of ancient philosophers.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Plato; Aristotle; Ethics, Ancient; Virtue; Reason